Sex‐specific analysis post‐liver transplantation in hemochromatosis with aplastic anemia and hepatocellular carcinoma. Issue 1 (11th November 2017) - Adams, Paul; Howlett, Christopher; Xenocostas, Anargyros; Chakrabarti, Subrata
Abstract : Telemedicine and Telehealth is changing the way we deliver care to our patients in far corners of our immediate and distant community. Harnessing the power of telehealth is key to extending academic expertise to patients and providers in underserved areas. Our article summarizes key aspects of telehealth based care in hepatology. Abstract : A 42‐year‐old man with hemochromatosis and cirrhosis developed aplastic anemia. He underwent liver transplantation from a female donor and splenectomy, and his aplastic anemia spontaneously resolved. A bone marrow examination 6 months after the liver transplant showed 17.5% female cells. He did well for 13 years without the need for any blood product support but then developed bone pain and was found to have metastatic hepatocellular carcinoma in the vertebral bodies. Molecular analysis demonstrated that the tumor cells were from his original liver. No primary liver tumor was identified in the explant. The case demonstrates the application of fluorescent in situ hybridization with X and Y chromosome‐specific probes to study chimerism and tumor origin after liver transplantation between individuals of different sex. ( Hepatology Communications 2018;2:13–15)